Quartz mineral purification flotation agent
Patent Information
- Application Number
- CN202511590481.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-03
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2045-11-03
AI Technical Summary
Existing quartz flotation technology cannot efficiently remove lattice impurities, resulting in product purity that cannot reach the 5N level. Furthermore, traditional collectors do not differentiate between minerals such as quartz, feldspar, and mica, leading to complex processes and high reagent consumption.
A combination of flotation agents, consisting of nano-space barrier dispersants, phosphate ester directional anchoring agents, weak lattice surface integrators, targeted multifunctional collectors, and microbubble synergistic frothers, is used to achieve precise collection of quartz lattice impurities and suppression of fine mud covering through stepwise addition and specific processes.
It achieves a 5N purity for quartz concentrate, with Al2O3 and Fe2O3 removal rates exceeding 98%, reducing ineffective adsorption of reagents, simplifying the process, and lowering reagent usage. Meanwhile, wastewater can be recycled, making it environmentally friendly and highly efficient.
Smart Images

Figure CN121244401B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of non-metallic mineral purification and processing technology, specifically to a quartz mineral purification flotation agent. Background Technology
[0002] High-purity quartz is an indispensable key basic material for modern electronic information, photovoltaic energy and high-end optical industries. Its core quality lies in the purity of SiO2, which must reach the level of 99.99% (4N) to 99.999% (5N).
[0003] Impurities such as aluminum and iron in quartz do not always exist as independent mineral inclusions. A significant portion, especially aluminum, replaces silicon atoms in the quartz lattice in an isomorphous manner. This substitution occurs at the atomic scale, making the impurity atoms an integral part of the quartz crystal structure. Traditional flotation reagents, such as the cationic collector dodecylamine, rely primarily on electrostatic adsorption and the hydrophobicity of molecular chains. They are effective at collecting independent aluminum-containing minerals exposed on the mineral surface, but are almost powerless against aluminum already embedded within the quartz lattice.
[0004] The aforementioned lattice impurities cannot be removed by physical sorting or conventional surface chemical reactions. Even after multiple flotation processes, the aluminum content in the concentrate generally remains above 100-200 ppm, making it difficult to achieve a removal rate exceeding 95%. This limits the final product purity to the 4N level, failing to meet the aluminum content requirements for ultra-high purity applications of 5N and above.
[0005] Furthermore, currently widely used industrial quartz flotation collectors, such as dodecylamine, primarily rely on the electrostatic attraction between their cationic head groups and the negatively charged regions of the mineral surface for their collecting effect. However, in complex systems where silicate minerals such as quartz, feldspar, and mica coexist, the surface potentials of these minerals are all negative at a given pH value, and the differences are minimal. Therefore, dodecylamine exhibits almost indiscriminate adsorption on various minerals such as quartz, feldspar, and mica. This broad-spectrum rather than targeted collecting behavior leads to drawbacks such as concentrate contamination, complex processes, and high reagent consumption.
[0006] Therefore, we propose a quartz mineral purification flotation agent to solve the problems mentioned above.
[0007] The information disclosed above in this background section is only for enhancing the understanding of the background section of this invention, and therefore may include prior art that is not known to those skilled in the art. Summary of the Invention
[0008] The purpose of this invention is to provide a quartz mineral purification flotation agent to solve the problem mentioned in the background art that the current quartz flotation technology on the market cannot simultaneously and efficiently remove lattice impurities, suppress fine mud covering, and achieve accurate flotation.
[0009] To achieve the above objectives, the present invention provides a quartz mineral purification flotation agent, which is made of the following components in parts by weight: 80-150 parts of nano-space barrier dispersant, 10-30 parts of phosphate ester directional anchoring agent, 150-300 parts of weak lattice surface integrator, 60-120 parts of targeted multifunctional collector, and 20-50 parts of microbubble synergistic foaming agent.
[0010] Preferably, the nano-space barrier dispersant is a composite of sodium polyacrylate and polyethylene glycol modified nano-SiO2, wherein the particle size of polyethylene glycol modified nano-SiO2 is 50-100 nm, the number average molecular weight of polyethylene glycol chains is 300-600, and the mass ratio of sodium polyacrylate to polyethylene glycol modified nano-SiO2 is 3:1-5:1.
[0011] Preferably, the phosphate ester directional anchoring agent is a mixture of monoalkyl phosphate and dodecyl phosphate, with a mass ratio of 1:1 to 1:3; and it has a good effect on the Al content of feldspar surfaces. 3+ The adsorption capacity is more than 5 times that of the quartz surface.
[0012] Preferably, the weak lattice surface integrator is a compound aqueous solution of aminosulfonic acid, citric acid and tartaric acid, with the mass percentages of the three being 40%-60%: 20%-40%: 10%-30%, and the pH value of the compound aqueous solution is 1.0-1.5.
[0013] Preferably, the targeted multifunctional collector is a chitosan-dodecylamine-EDTA graft copolymer, wherein the molar ratio of chitosan, dodecylamine, and EDTA is 4:2-4:1-3, the number average molecular weight of the graft copolymer is 6000-10000, and the water solubility at 25°C is ≥10g / L.
[0014] Preferably, the targeted multifunctional collector is a physical compound of chitosan, dodecylamine and disodium EDTA, with a mass ratio of 2:1.5:1 to 2:0.5:0.5.
[0015] Preferably, the microbubble synergistic foaming agent is a mixture of castor oil polyoxyethylene ether with an ethylene oxide addition number of 5-15 and polyethylene glycol, wherein the mass ratio of castor oil polyoxyethylene ether to polyethylene glycol is 1.5:1-2.5:1, and the number average molecular weight of polyethylene glycol is 300-500.
[0016] The application process of quartz mineral purification flotation agents includes the following steps:
[0017] S1. Crush and grind the raw quartz ore to a particle size of -0.074mm with a proportion of 85%-95% to obtain a slurry;
[0018] S2. Add nano-space barrier dispersant to the slurry to make the slurry concentration 28%-35%, stir for 2-4 minutes, and adjust the pH of the slurry to 7.0-8.5;
[0019] S3. Add phosphate ester directional anchoring agent to the slurry treated in step S2, and stir for 2-3 minutes;
[0020] S4. Add a weak lattice surface integrator to the slurry treated in step S3, and stir for 4-6 minutes.
[0021] S5. Add the targeted multifunctional collector to the slurry treated in step S4, and stir for 3-5 minutes.
[0022] S6. Add microbubble synergistic frother to the slurry treated in step S5, introduce air and use a jet-type microbubble generator to generate bubbles for flotation operation;
[0023] S7. Collect the bottom product after flotation, and after dehydration and drying, obtain ultra-high purity quartz concentrate;
[0024] S8. The flotation wastewater is subjected to neutralization precipitation, Fenton oxidation and activated carbon adsorption treatment in sequence. The treated water is reused for grinding in step S1 or slurry preparation in step S2.
[0025] Preferably, in step S6, the operating pressure of the jet-type microbubble generator is 0.3-0.5 MPa, and the Sotter average diameter of the generated bubbles is 5-15 μm; the flotation operation consists of three stages: roughing, cleaning, and scavenging, wherein the aeration rate for roughing is 0.18-0.22 m³ / s. 3 / (m 2 •min), with a selected inflation volume of 0.12-0.16m³. 3 / (m 2 ·min).
[0026] Compared with the prior art, the beneficial effects of the present invention are:
[0027] This invention introduces a weak lattice surface integrator that, under low pH conditions, can selectively react with Al, which exists in an isomorphic form on the quartz surface and subsurface layer. 3+ Fe 3+Impurity ions undergo chelation reactions to form soluble complexes, thereby stripping them from the edges of the quartz lattice and transforming them into floatable free ions or active sites. Subsequently, the targeted multifunctional collector, through its functional groups such as EDTA groups, efficiently captures these stripped impurity ions and carries them into the foam product via hydrophobic chains. This solves the problem of traditional flotation's inability to handle lattice impurities.
[0028] The phosphate ester directional anchoring agent of the present invention has an effect on Al on the feldspar surface. 3+ The sites exhibit extremely strong specific adsorption capacity, preferentially forming hydrophobic films on the surfaces of gangue minerals such as feldspar. Furthermore, the targeted multifunctional collector itself possesses designable molecular structures; through specific grafting or compounding of chitosan, dodecylamine, and EDTA in particular ratios, it can precisely identify and adsorb onto specific mineral surfaces. This dual targeting effect results in highly precise collection behavior, significantly reducing ineffective adsorption of the agent on the quartz surface.
[0029] The nano-space barrier dispersant used in this invention constructs a stable nano-barrier in the slurry through the electrostatic repulsion of sodium polyacrylate and the strong steric hindrance effect formed after the nanoparticles are adsorbed on the mineral surface, effectively preventing the physical covering of fine clay particles on the quartz surface.
[0030] The dispersant, anchoring agent, integrator, collector, foaming agent, and their stepwise addition process of the present invention avoid mutual interference between the agents, resulting in an enhanced synergistic effect. Simultaneously, the system is a fluorine-free and non-toxic or low-toxic formulation, and through a matching wastewater treatment and reuse process, it achieves environmentally friendly wastewater recycling.
[0031] The above overview is for illustrative purposes only and is not intended to be limiting in any way. In addition to the illustrative aspects, embodiments, and features described above, further aspects, embodiments, and features of the invention will become readily apparent from the accompanying drawings and the following detailed description. Attached Figure Description
[0032] Figure 1 This diagram illustrates the effect of the quartz mineral purification flotation agent of the present invention on the mineral solution interface.
[0033] Figure 2 This is a process flow diagram of the quartz mineral purification flotation agent of the present invention. Detailed Implementation
[0034] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. It should be noted that the drawings are schematic and not illustrated to scale. For clarity and convenience, the relative sizes and proportions of the parts shown in the drawings have been exaggerated or reduced in size. Any size is only illustrative and not limiting.
[0035] Please see Figures 1-2 Example 1: Purification of high-alumina iron ore quartz
[0036] The ore originates from granite pegmatite-type quartz deposits, with the following chemical composition: SiO2 99.92%, Al2O3 0.21%, Fe2O3 0.08%, Ti2O5 0.03%. Fine clay (-20μm) accounts for 32% of the composition, and feldspar and mica are embedded in the quartz crystals, mostly in the 10-30μm range. XPS analysis indicates that approximately 60% of the Al exists isomorphously within the quartz lattice.
[0037] Flotation agent formulation: 120g / t of nano-space barrier dispersant, specific composition: 96g / t of sodium polyacrylate, 24g / t of PEG-400 modified nano-SiO2 with a particle size of 80nm, mass ratio 4:1.
[0038] The phosphate ester directional anchoring agent is 20g / t, specifically composed of: 6.7g / t monoalkyl phosphate ester and 13.3g / t dodecyl phosphate ester, in a mass ratio of 1:2.
[0039] The weak lattice surface integrator 200g / t is specifically composed of: 50% sulfamic acid 100g / t, 30% citric acid 60g / t, and 20% tartaric acid 40g / t, prepared as an aqueous solution with pH=1.2.
[0040] Targeted multifunctional collector: 100g / t. Utilizing a graft copolymer formulation, chitosan:dodecylamine:EDTA molar ratio = 4:3:2, number average molecular weight 8000.
[0041] Microbubble synergistic foaming agent: 30g / t, specific composition: castor oil polyoxyethylene ether EL-10 (EO number = 10) 20g / t, polyethylene glycol 400 (PEG-400) 10g / t, mass ratio 2:1.
[0042] The application process of quartz mineral purification flotation agents includes the following steps:
[0043] S1. Grind the ore to -0.074mm (200 mesh) with 90% of the particles, and prepare a slurry with a concentration of 32%.
[0044] S2. Add dispersant, adjust the pH of the slurry to 8.0 using NaOH solution, and stir vigorously at 1500 rpm for 3 min. After stirring, the zeta potential of the slurry was measured to be -42 mV using a nanoparticle size analyzer and a zeta potential meter.
[0045] S3. Add anchoring agent and gently stir at 800 rpm for 2 minutes.
[0046] S4. Add the integrator and stir at 1000 rpm for 5 minutes until the pH of the system drops to 4.5.
[0047] S5. Add the collector and stir at 1000 rpm for 4 minutes.
[0048] S6. Add frother and introduce it into a jet-type microbubble generator for three-stage flotation. The aeration rate for the roughing stage is 0.20 m³ / s. 3 / (m 2 •min), with a selected inflation volume of 0.15m 3 / (m 2 •min))Sweeping air volume 0.18m 3 / (m 2 (min), and add 8g / t of collector. The flotation temperature is controlled at 28℃.
[0049] S7. The bottom product of the flotation tank is vacuum filtered and dried at 105℃ to obtain concentrate. The flotation wastewater is neutralized with lime, Fenton oxidation, and activated carbon filtration. The COD is measured to be 78 mg / L, and it is reused for grinding with a reuse rate of 85%.
[0050] The final purified concentrate chemical composition was: SiO2 99.9992%, Al2O3 28ppm, Fe2O3 4.5ppm, Ti2O 59ppm. The Al2O3 removal rate was 98.7%, the Fe2O3 removal rate was 99.4%, and the fine mud coverage rate was 9.2% as determined by scanning electron microscopy.
[0051] Example 2: Purification of high-fineness mud-content quartz using a physically compounded collector.
[0052] The original ore is a weathered sedimentary quartz sand deposit with the following chemical composition: SiO2 99.89%, Al2O3 0.25%, Fe2O3 0.06%. Among them, the content of -20μm fine mud is as high as 40%, the original ore is severely muddy, and the feldspar is highly weathered.
[0053] Flotation reagent formulation: Targeted multifunctional collector: A physical compound formulation is adopted, totaling 110 g / t. Among them, chitosan with a degree of deacetylation of 95% is 50 g / t, dodecylamine is 35 g / t, and disodium EDTA is 25 g / t, with a mass ratio of 2:1.4:1.
[0054] The nano-space barrier dispersant is 150 g / t, comprising 120 g / t sodium polyacrylate and 30 g / t PEG-modified nano-SiO2. The remaining formulations are the same as in Example 1.
[0055] In the application process of the quartz mineral purification flotation agent, the pulp pH in step S2 is 8.5; in step S6, 10% (11g / t) of collector is added for scavenging, and the remaining steps are the same as in Example 1.
[0056] The final purified concentrate chemical composition was: SiO2 99.9990%, Al2O3 26 ppm, Fe2O3 3.8 ppm. The Al2O3 removal rate was 99.0%, and the fine mud coverage rate was 11.5%.
[0057] As can be seen from the above, despite the worse conditions of the raw ore, the purity of 5N was still achieved by increasing the amount of dispersant and using a physically compounded collector.
[0058] Example 3: Purification of high-titanium impurity quartz
[0059] The original ore is derived from hydrothermal vein-type quartz deposits, with rutile as an associated mineral.
[0060] Chemical composition: SiO2 99.93%, Al2O3 0.18%, Fe2O3 0.05%, Ti2O5 0.04%. Among them, Ti exists in the form of fine rutile, and part of it isomorphously replaces Si in quartz.
[0061] Flotation reagent ratio: The ratio of weak lattice surface integrator to acid is 45% aminosulfonic acid, 35% citric acid, and 20% tartaric acid.
[0062] The dosage of the phosphate ester directional anchoring agent was increased to 25 g / t (mono / dodecyl phosphate = 1:1.5). The remaining reagents and formulations are the same as in Example 1.
[0063] The final purified concentrate has the following chemical composition: SiO2 99.9994%, Al2O3 22ppm, Fe2O3 4.0ppm, and Ti2O5 8ppm. The Ti2O5 removal rate is 98.0%, higher than conventional flotation, demonstrating that this invention also has a highly efficient removal capability for titanium impurities.
[0064] Example 4: Treatment of low-grade, high-impurity, and difficult-to-select quartzite
[0065] The raw ore comes from quartzite, with the following chemical composition: SiO2: 99.65%, Al2O3: 0.28%, Fe2O3: 0.12%, K2O: 0.09%, Na2O: 0.06%, TiO2: 0.02%, CaO+MgO: 0.03%. The main gangue minerals are microcline and muscovite, with small amounts of tourmaline, chlorite, and hematite. The quartz and these impurity minerals are unevenly distributed in grain size, mostly between 10-50 μm, with some mica flakes having a grain size <5 μm. After grinding to a point where -0.074 mm accounts for 92%, the content of -20 μm fine clay reaches 38%, indicating significant clayification.
[0066] Flotation agent formulation: 150 g / t of nano-space barrier dispersant. Specifically: 120 g / t of sodium polyacrylate, and PEG-400 modified nano-SiO2 (particle size 80 nm, grafting density 0.6 chains / nm). 2 30g / t. Premix well before use.
[0067] Phosphate ester directional anchoring agent 30g / t. It is a compound of monoalkyl phosphate ester and dodecyl phosphate ester.
[0068] Weak lattice surface integrator 280g / t. Prepare an aqueous solution with pH=1.2 according to the ratio of aminosulfonic acid (50%) 140g / t, citric acid (30%) 84g / t, and tartaric acid (20%) 56g / t.
[0069] Targeted multifunctional collector 120g / t. A physical compound formulation is used, consisting of 55g / t chitosan (95% deacetylation, viscosity 100-200 mPa·s), 40g / t dodecylamine, and 25g / t disodium EDTA. These three components are dissolved in water at room temperature to prepare a 5% mixed solution before use.
[0070] Microbubble synergistic foaming agent 40g / t. Castor oil polyoxyethylene ether EL-102 6.7g / t and PEG-400 13.3g / t were mixed.
[0071] The application process of quartz mineral purification flotation agents includes the following steps:
[0072] S1. Three-stage grinding system: rod mill - ball mill, ensuring 92% of the material is -0.074mm while reducing over-grinding.
[0073] S2. In a 30% concentration mineral slurry, a dispersant was added, and the pH was adjusted to 8.2 with NaOH solution. The mixture was then vigorously stirred at 1500 rpm for 4 minutes. After stirring, the zeta potential of the slurry supernatant was measured to be -44 mV, indicating good dispersion.
[0074] S3-S5. Add anchoring agent, integrator and collector in sequence, and set the stirring time to 3 min, 6 min and 5 min respectively.
[0075] S6. A coarse, fine, and sweep process is adopted. The coarse selection inflation volume is 0.22m³. 3 / (m 2 (·min), the air volume of Selected I and II is 0.16 and 0.14 m³, respectively. 3 / (m 2 •min). To fully recover impurities, 12g / t of collector (10% of the total amount) was added to both scavenging stages I and II. A jet microbubble generator (pressure 0.45MPa) was used throughout the process.
[0076] The final purified concentrate has the following chemical composition: SiO2: 99.9985%, Al2O3: 35ppm, Fe2O3: 6ppm, K2O: <5ppm, Na2O: <5ppm.
[0077] The Al2O3 removal rate was (0.28% - 0.0035%) / 0.28% × 100% = 98.75%. The Fe2O3 removal rate was (0.12% - 0.0006%) / 0.12% × 100% = 99.50%.
[0078] Randomly selected concentrate particles were observed using scanning electron microscopy. The particles had smooth surfaces with very little attached fine mud, and the fine mud coverage rate was approximately 10.5%. The Hunter whiteness value of the concentrate powder after drying at 105℃ was 96.2, indicating that coloring impurities such as iron and titanium were effectively removed.
[0079] Example 5: Functional Alternatives for Key Components
[0080] Select the same raw ore as in Example 1.
[0081] Flotation agent formulation: In the nano-space barrier dispersant, sodium polyacrylate is replaced with polyacrylamide, and PEG-modified nano-SiO2 is replaced with PEG-modified nano-TiO2. Polyacrylamide and PEG-modified nano-TiO2 are compounded at a mass ratio of 4:1, with a total dosage of 120 g / t. Sodium lauryl sarcosinate is used as the phosphate ester directional anchoring agent, with a dosage of 25 g / t. The remaining reagents, their order of addition, and process parameters are consistent with those in Example 1.
[0082] The final purified concentrate has the following chemical composition: SiO2 99.9990%, Al2O3 30ppm, Fe2O3 5ppm.
[0083] Example 6: The Influence of Changing Process Parameters
[0084] The same raw ore as in Example 1 was selected, and the flotation reagent ratio was exactly the same as in Example 1.
[0085] The difference between the application process of the quartz mineral purification flotation agent and Example 1 is as follows:
[0086] S2. After adding the dispersant, no more NaOH was used to adjust the alkali; instead, the natural pH of the slurry was maintained. The mixture was stirred for 3 minutes under these conditions. Monitoring showed that the zeta potential still reached -35mV, indicating that the dispersant was still effective under weakly acidic conditions, but its effect was slightly less than under alkaline conditions.
[0087] S3. Add anchoring agent and stir for 2 minutes. Adjust the pH of the slurry to 4.0 precisely using dilute sulfuric acid.
[0088] S4. Add the integrator at pH 4.0 and stir for 5 minutes.
[0089] S5 targeted trapping and S6 microbubble flotation were carried out at pH 4.0.
[0090] The final purified concentrate chemical composition was: SiO2 99.9988%, Al2O3 33ppm, Fe2O3 5.5ppm.
[0091] Compared with Example 1, the product purity remains extremely high, but the Al2O3 and Fe2O3 contents are slightly higher than in Example 1. This proves that the present invention is completely feasible and effective in an acidic range of pH 4.0-5.5.
[0092] Comparative Example 1 simulates the common fluorine-free flotation technology in the current industry and compares its overall purification effect with that of the present invention.
[0093] Experimental method: The same batch of quartz ore was used for the raw ore and the same batch used in Example 1.
[0094] Chemical formulation: Dodecylamine as collector: 150g / t; Water glass as inhibitor: 2000g / t; Pinyl alcohol oil as foaming agent: 50g / t.
[0095] Dosing process: Water glass and dodecylamine are added to the pulp simultaneously and stirred at 1000 rpm for 5 minutes. Then, pine oil is added and stirred for 1 minute. Roughing, cleaning, and scavenging flotation are performed in a conventional mechanically stirred flotation machine, with the aeration rate uniformly controlled at 0.20 m³ / min. 3 / (m 2 (min), no microbubble generator was used.
[0096] Analysis and Testing: After flotation, the concentrate from the bottom of the tank was collected, filtered and dried under the same conditions, and then sent for ICP-OES analysis of its composition. Samples were also taken for scanning electron microscopy (SEM) analysis to determine the fine mud coverage rate. The experimental data are shown in Table 1.
[0097] detection indicators Example 1 Comparative Example 1 <![CDATA[SiO₂ Purity (%)]]> 99.9992 99.985 <![CDATA[Al2O3 content (ppm)]]> 28 165 <![CDATA[Fe2O3 content (ppm)]]> 4.5 52 <![CDATA[Al2O3 removal rate (%)]]> 98.7 92.1 <![CDATA[Fe2O3 removal rate (%)]]> 99.4 93.5 Fine mud coverage rate (%) 9.2 51.0
[0098] Table 1
[0099] Results Analysis: The quartz concentrate obtained in Comparative Example 1 had a purity of only 99.985%, far below the 99.999% 5N standard. The removal rates of Al₂O₃ and Fe₂O₃ in Comparative Example 1 were both below 94%, indicating that its collection of surface impurities was incomplete, and it was ineffective against lattice impurities. Furthermore, the high fine mud coverage rate of 51% proves that simply using water glass cannot solve the problem of fine particle interference.
[0100] Comparative Example 2 verifies the necessity of the application process of the quartz mineral purification flotation agent of the present invention.
[0101] Experimental method: The same batch of quartz ore was used for the raw ore and the same batch used in Example 1.
[0102] Flotation reagents: Reagent formulation: The types and total mass of reagents used are the same as in Example 1.
[0103] Dosing process: The nano-space barrier dispersant, phosphate ester directional anchoring agent, weak lattice surface integrator, and targeted multifunctional collector were mixed in a batching tank before flotation. The mixed reagents were then added to the slurry all at once and stirred at 1000 rpm for 8 minutes. Subsequently, a microbubble synergist was added, and the same three-stage microbubble flotation process as in Example 1 was performed. Analysis and testing were performed as in Comparative Example 1. Experimental data are shown in Table 2.
[0104] detection indicators Example 1 Comparative Example 2 <![CDATA[SiO₂ Purity (%)]]> 99.9992 99.993 <![CDATA[Al2O3 content (ppm)]]> 28 82 <![CDATA[Fe2O3 content (ppm)]]> 4.5 25 <![CDATA[Al2O3 removal rate (%)]]> 98.7 96.1 Fine mud coverage rate (%) 9.2 35.0
[0105] Table 2
[0106] Results Analysis: Despite using the exact same reagents as in this invention, the purification effect of the single-dosing method was significantly reduced. Al₂O₃ content increased from 28 ppm to 82 ppm, and the fine mud coverage also increased from 9.2% to 35.0%. Single-dosing leads to interference between reagent functions. The strongly acidic integrator disrupts the spatial barrier effect of the dispersant and neutralizes the cationic collector; furthermore, the dispersant hinders the adsorption of the anchoring agent and collector on the target mineral surface. Therefore, the stepwise process of this invention ensures that the reagents in each step function under optimal conditions, and that the preceding steps create a favorable surface environment for subsequent steps.
[0107] In summary, the five core components of this invention and their step-by-step addition process are scientifically and rationally designed. Each step creates optimal conditions for the next, avoiding mutual interference between reagents and generating an enhanced synergistic effect. Furthermore, this system is a fluoride-free and non-toxic or low-toxic formulation, and through a matching wastewater treatment and reuse process, it achieves a wastewater COD value below 80 mg / L and a high reuse rate.
[0108] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0109] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A flotation agent for purifying quartz minerals, characterized in that, It is made from the following components in parts by weight: 80-150 parts of nano-space barrier dispersant, 10-30 parts of phosphate ester directional anchoring agent, 150-300 parts of weak lattice surface integrator, 60-120 parts of targeted multifunctional collector, and 20-50 parts of microbubble synergistic foaming agent. The nano-space barrier dispersant is a composite of sodium polyacrylate and polyethylene glycol modified nano-SiO2, wherein the particle size of polyethylene glycol modified nano-SiO2 is 50-100nm, the number average molecular weight of polyethylene glycol chains is 300-600, and the mass ratio of sodium polyacrylate to polyethylene glycol modified nano-SiO2 is 3:1-5:
1. The phosphate ester directional anchoring agent is a mixture of monoalkyl phosphate and dodecyl phosphate, with a mass ratio of 1:1 to 1:3; and it has a strong effect on the Al content of feldspar surfaces. 3+ The adsorption capacity is more than 5 times that of the quartz surface; The weak lattice surface integrator is a compound aqueous solution of aminosulfonic acid, citric acid and tartaric acid, with a mass percentage of 40%-60%: 20%-40%: 10%-30%, and the pH value of the compound aqueous solution is 1.0-1.
5. The targeted multifunctional collector is a chitosan-dodecylamine-EDTA graft copolymer, wherein the molar ratio of chitosan, dodecylamine and EDTA is 4:2-4:1-3, the number average molecular weight of the graft copolymer is 6000-10000, and the water solubility at 25℃ is ≥10g / L. The targeted multifunctional collector is a physical compound of chitosan, dodecylamine and disodium EDTA, with a mass ratio of 2:1.5:1-2:0.5:0.
5. The microbubble synergistic foaming agent is a mixture of castor oil polyoxyethylene ether with an ethylene oxide addition number of 5-15 and polyethylene glycol, wherein the mass ratio of castor oil polyoxyethylene ether to polyethylene glycol is 1.5:1-2.5:1, and the number average molecular weight of polyethylene glycol is 300-500.
2. The application process of the quartz mineral purification flotation agent according to claim 1, characterized in that, Includes the following steps: S1. Crush and grind the raw quartz ore to a particle size of -0.074mm with a proportion of 85%-95% to obtain a slurry; S2. Add nano-space barrier dispersant to the slurry to make the slurry concentration 28%-35%, stir for 2-4 minutes, and adjust the pH of the slurry to 7.0-8.5; S3. Add phosphate ester directional anchoring agent to the slurry treated in step S2, and stir for 2-3 minutes; S4. Add a weak lattice surface integrator to the slurry treated in step S3, and stir for 4-6 minutes. S5. Add the targeted multifunctional collector to the slurry treated in step S4, and stir for 3-5 minutes. S6. Add microbubble synergistic frother to the slurry treated in step S5, introduce air and use a jet-type microbubble generator to generate bubbles for flotation operation; S7. Collect the bottom product after flotation, and after dehydration and drying, obtain ultra-high purity quartz concentrate; S8. The flotation wastewater is subjected to neutralization precipitation, Fenton oxidation and activated carbon adsorption treatment in sequence. The treated water is reused for grinding in step S1 or slurry preparation in step S2.
3. The application process of the quartz mineral purification flotation agent according to claim 2, characterized in that: In step S6, the operating pressure of the jet-type microbubble generator is 0.3-0.5 MPa, and the Sotter average diameter of the generated bubbles is 5-15 μm; the flotation operation consists of three stages: roughing, cleaning, and scavenging, with the roughing aeration rate being 0.18-0.22 m³ / s. 3 / (m 2 •min), with a selected inflation volume of 0.12-0.16m³. 3 / (m 2 ·min).
Citation Information
Patent Citations
Preparation method of instant anionic polyacrylamide
CN119930917A
Production process for recycling waste glass
CN120662615A
